Ausferritic (bainitic) cast iron: Harmonization of international standard ISO 17804 in application to the conditions of Belarus - A. I. Pokrovskii; B. B. Khina; O. A. Tolkacheva (Литьë и металлургия)
The experience of the Physico-technical Institute (PhTI) of the National Acdemy of Sciences of Belarus in the harmonization of international standard ISO 17804 (Founding – Ausferritic spheroidal graphite cast irons – Classification) and development of the Belorussian analogue STB ISO is described. The reasons for the choice of austempered ductile iron (ADI) as an object for standard harmonization are presented: it is the most promising cast iron in comparison with gray and classical ductile iron. The work procedure on harmonization is described: how to include the task into the State Plan on standardization, specificity of translation of the text, peculiarities of with state organizations responsible for approbation of standards such as Belorussian Institute for Standardization and Certification (BelGISS) and State Committee on Standards (Gosstandart), writing a summary of external reviews, working with critical comments from potential users. It is outlined that any foreign standard does not exists independently but is closely connected with at least 10 to 20 other standards. Thus, harmonization necessitates coordination with other standards and sometimes even with handbooks by adding annexes to the main text. The importance of a proper choice of the standard status is outlined: identical (ID) or modified (MOD). Developing an identical standard is prestigious but difficult because is requires harmonization of all the referenced standards, which is a very labor-consuming procedure. It is argued that the most suitable is ‘intermediate’ variant: adopting the authentic text of the international standard (in high-quality translation) but with annexes reflecting national specificity in this area. As a result, a harmonized standard is developed which, for the first time in Belarus, standardize the tensile strength of 800 MPa in combination with the elongation of 10 % and the tensile strength of 1400 MPa in combination with the elongation of 1 % for cast irons.The annual demand for ADI in Belarus is estimated as about 10,000 ton. It is shown that in Belarus, where about 60 industrial enterprises have a foundry and almost every engineering plant has a heat-treatment shop, austempered ductile cast (ADI), which features a high strength, can successfully compete with rolled steel in certain applications.